SCAR Persistent Organic Pollutants Database ... - Scientific Committee On Antarctic Research (Zenodo, 2023)
A compilation of persistent organic pollutant data from Antarctica and the Southern Ocean, entered from journal and other publications. This database is accompanied by an interactive data exploration app at https://pops.apps.aq/ Data table schemas Sources data table - source_id: The unique identifier of this source - source_details: The bibliographic details for this source - source_notes: Relevant notes about this source – if it’s a published paper, this is probably the abstract - source_doi: The DOI of the source (paper or dataset), in the form "10.xxxx/yyyy" Main data table - source_id: The identifier of the source study from which this record was obtained (see corresponding entry in the sources data table) - original_record_id: The identifier of this data record in its original source, if it had one - location: The name of the location at which the data was collected - west: The westernmost longitude of the sampling region, in decimal degrees (negative values for western hemisphere longitudes) - east: ...